PENGARUH PROFITABILITY, FIRM SIZE, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Arya, Arya; Suhendah, Rousilita (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to obtain empirical evidence regarding the effect of profitability, firm size, and leverage on financial distress. This study used manufacturing companies listed on the IDX during 2017-2019. The sample was selected using the purposive sampling method and the data that met the criteria were 69 companies. The data obtained was then processed using Microsoft Excel 2016 and Eviews 10 software. Based on the results obtained in this study, it was found that profitability, firm size, and leverage together have an effect on financial distress. Individually, profitability and leverage have no effect on financial distress. Meanwhile, firm size has a negative effect on financial distress.